Survival Rate and Growth of Economical Fishes in Tailing Ponds of Bauxite Post-mining in Senggarang, Tanjungpinang City - Irvan Hasan Ashari; Tri Apriadi; Winny Retna Melani (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2019)
The tailing pond of bauxite post-mining in Senggarang, Tanjungpinang City, have been potency of natural feed sources from phytoplankton and zooplankton. Moreover, the water quality of the tailing pond of bauxite post-mining has begun to support fish life. The objective of this study was to determine the survival rate and growth of economical fish in tailings ponds of bauxite post-mining in Senggarang, Tanjungpinang. The research was conducted by field experiment using a completely randomized design. There were different fish varieties as treatment: tilapia (Oreochromis niloticus), gouramy (Osphronemus gouramy), and tambaqui (Colossoma macropomum). Every treatment was carried out 5 replications, with 6 fish in every cage replication. Monitoring the water quality and the fish survival on the 0th, 10th, 20th and 30th days. The survival of economical fishes in tailing ponds of bauxite post-mining from the highest to lowest were tambaqui (97%), tilapia (83%), and gouramy (40%), respectively. The growth of fishes length from the highest to the lowest were gouramy (0,223 cm), tambaqui (0,037 cm), and tilapia (0,018 cm). Meanwhile, all variety of fish tested had a decreased in weigh: gouramy -0,2310 grams, tilapia -0,4281 grams, and tambaqui -1,3498 grams. The management of tailing ponds of bauxite post-mining in Senggarang for fisheries activities can be carried out by tambaqui (C. macropomum) culture cage with several conditions such as measurement of carrying capacity and capacity, management of water quality, feed, and technical aspects of culture.Keywords: bauxite, economical fish, growth, survival rate, tailing ponds